STRATEGI KOMUNIKASI PARTAI POLITIK MELALUI MEDIA SOSIAL DALAM MENINGKATKAN POPULARITAS DAN ELEKTABILITAS: (Studi Pengelolaan Media Sosial DPP Partai NasDem) - Holilah, Ilah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
Political communication is a form of message delivery characterized by political messages with the aim of influencing the masses. The presence of social media is certainly used as a communication tool by political parties, legislative candidates, government and activists. Social media plays an important role in letting political parties inform the general public about their political activities. Social media is used for political purposes by political parties because with social media the audience can be easily influenced. The aim of this research is to find out how the NasDem political party manages its social media to communicate with the public, especially in terms of increasing the party's popularity and electability. The method used in this research is a qualitative research method with a sociological approach. The object of this research is the social media of the NasDem Party, which is one of the political parties in Indonesia. The data needed in this research is divided into 2 (two) sources, namely primary data and secondary data. The methods used to search for data in this research were observation, interviews and document study. Based on the research results, it can be concluded that the unanimous strategy of the National Democratic Political Party (NasDem) in its efforts to provide a boost to its electoral electability is considered to be running smoothly, and the results benefit the NasDem political party itself. So that the NasDem Political Party has succeeded in proving its ability to compete with other major political parties in Indonesia.